Multicenter Study of Carbon-Ion Radiation Therapy for Adenoid Cystic Carcinoma of the Head and Neck: Subanalysis of the Japan Carbon-Ion Radiation Oncology Study Group (J-CROS) Study (1402 HN) - Sulaiman, Nor Shazrina; Demizu, Yusuke; Koto, Masashi; Saitoh, Jun-ichi; Suefuji, Hiroaki; Tsuji, Hiroshi; Ohno, Tatsuya; Shioyama, Yoshiyuki; Okimoto, Tomoaki; Daimon, Takashi; Nemoto, Kenji; Nakano, Takashi; et al. (International journal of radiation oncology, biology, physics, 2018)
To retrospectively analyze the treatment outcomes of carbon-ion radiation therapy for adenoid cystic carcinoma (ACC) of the head and neck at 4 active carbon-ion facilities in Japan. A total of 289 patients who underwent carbon-ion radiation therapy for histology-proven ACC of the head and neck at 4 institutions in Japan between November 2003 and December 2014 were included in this study. Median patient age was 58 years (range, 12-83 years). Tumor sites included the nasal cavity and paranasal sinuses (42%), nasopharynx and oropharynx (19%), oral cavity (12%), major salivary glands (12%), and others (15%). Tumor classifications were T4 in 200 (69%) patients, T3 in 45 (16%), T2 in 22 (8%), T1 in 15 (5%), and unclassified in 7 (2%). The median total dose was 64 Gy (relative biological effectiveness [RBE]; range, 55.2-70.4 Gy [RBE]) in 16 fractions (range, 12-32 fractions). Median follow-up time was 30 months (range, 2-118 months). The 2-year overall survival, progression-free survival, and local control rates were 94%, 68%, and 88%, respectively. Estimated 5-year overall survival, progression-free survival, and local control rates were 74%, 44%, and 68%, respectively. In all, 43 patients (15%) experienced grade ≥3 late toxicity, of which osteonecrosis of the jaw bone was the most common. Two patients treated for nasopharyngeal ACC died from a bleeding ulcer at the tumor site (grade 5 toxicity). Carbon-ion radiation therapy seems to be a promising treatment for ACC of the head and neck.